Penerapan Pijat Oksitosin untuk Meningkatkan Produksi Asi Ibu Menyusui pada Masa Nifas - Rosmiarti, Rosmiarti; Lestari, Santi (Ners Akademika, 2024)
Purpose: To provide comprehensive midwifery care for Mrs. "K" with the implementation of oxytocin massage to increase breast milk production in postpartum mothers. Research Method: The method used is a case study. The subject of this study is Mrs. "K.” Data collection techniques included interviews, observations, physical examinations, and the SOAP forms. The smoothness of breast milk production was assessed using 10 indicators, which were compared between patients who received treatment and those who did not receive oxytocin massage on day 3 postpartum. Results: After comprehensive midwifery care, neither the mother nor the baby experienced life-threatening issues. Oxytocin massage performed for 3 consecutive days, twice a day for 15-20 minutes, positively influenced breast milk production compared to those who did not receive the massage. Limitations: This study focused on a single case (Mrs. "K"), which limits the generalizability of the results to a broader population. A larger sample size is necessary to draw definitive conclusions. Contribution: This study demonstrates the practical application of oxytocin massage as an intervention to improve breast milk production in postpartum mothers, providing valuable insights for midwives and healthcare practitioners.